Immunohistochemistry as a diagnostic and prosnotic tool of hepatic preneoplastic lesions in rat hepatocarcinogenesis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Hepatic preneoplastic lesion refers to phenotypically altered cell populations, which have no obvious neoplastic nature, but have a high probability of progressing to a benign or malignant tumor. Theoretically these lesions could consist of a. Definitive tumor cells which are not as yet growing autonomously because of the influence of mechanisms residing outside the cells and b. Phenotypically altered cells which lack important properties of the final tumor cells. Immunohistochemistry successfully complements morphological studies for the identification and classification of tumors when performed with well-defined monoclonal antibodies. In continuation of earlier studies on rat preneoplastic liver lesions, we characterized by immunohistochemical method the phenotype of murine hepatic preneoplastic lesions in a cancer bioassay. The initiation-promotion protocol was used to test the hypothesis that the atherogenic diet (high lipid and high cholesterol) acts as a liver tumor promoter in male Sprague-Dawley rats after initiation with a single dose of N-nitrosodiethylamine (NDEA, 20 mg/kg bw, s.c.). The sites and times of appearance of preneoplastic lesions in the rat livers at the end of the experiment on day 90 were observed in the two separate experiments. The preneoplastic lesions of hepatocytes were composed predominantly of basophilic cells, with some distortion and compression of the adjacent hepatic parenchyma. The normal liver architecture is preserved, as indicated by the presence of central veins and portal triads. The immunohistochemical staining of all preneoplastic cells in the livers of the rats showed negative cells for cytokeratin 5, 6 and 18, expressed in anaplastic carcinomas. Several markers of hepatocellular differentiation may still need to be applied which are specific for hepatocellular carcinoma.